Academic Leaders in Al-Baydaa University Assessing the Strategic Performance by Using B.S.C - Al-Abidi, Safaa Nasser; Ameen, Abduljabar Altaeb; Al-Sharjabi, Abdulrahman Mohammed (Journal of Educational and Psychological Sciences, 2021)
This research aimed to evaluate the strategic performance of Al-Baydaa University by using BSC with its four perspectives (financial - clients’- internal processes - learning and growth, the researcher used the descriptive survey method, while it relied on Delphi method for data collection, the questionnaire applied to (17) experts was the tool. The research concluded the following results: The general assessment of the reality of the strategic performance of the University of Al-Baydaa got a total average (1.54 out of 3), with a degree (weak). At the level of dimensions, the beneficiaries dimension got the highest average (1.58), then the internal operations dimension with an average (1.56), and thirdly the financial performance dimension with an average (1.54), and finally the learning and growth dimension with an average (1.47), all of which came with a performance degree (weak) ranked. The researcher recommendation that universities must adoption BSC to evaluate and improve performance because it has a completely perspectives strategic tool, which needs availability necessary materialism and non- materialism potentials. It also made a number of proposals, including the need to study the requirements for developing the strategic performance appraisal system in Yemeni universities, "a qualitative field study."